The global trends and distribution in tumor-infiltrating lymphocytes over the past 49 years: bibliometric and visualized analysis - Wu, Beibei; Luo, Ding; Wang, Xuejie; Qiao, Chen; Li, Rui; Liu, Jian (Frontiers in immunology, 2025)
The body of research on tumor-infiltrating lymphocytes (TILs) is expanding rapidly; yet, a comprehensive analysis of related publications has been notably absent. This study utilizes bibliometric methodologies to identify emerging research hotspots and to map the distribution of tumor-infiltrating lymphocyte research. Literature from the Web of Science database was analyzed and visualized using VOSviewer, CiteSpace, Scimago Graphica, R-bibliometrix, and R packages. Research on tumor-infiltrating lymphocytes began in 1975 and has experienced significant growth, particularly after 2015. Leading contributors include the United States, the National Cancer Institute, the journal Cancer Immunology Immunotherapy, and researcher Steven A. Rosenberg. Other prominent contributors include China, the National Institutes of Health, researcher Roberto Salgado, and the Journal of Immunology. Prominent institutions in the USA and Europe occupy central roles within collaborative networks. Financial support plays a pivotal role in driving research advancements. Keyword clustering analysis reveals four primary knowledge domains: adoptive cell therapy; the prognostic value of TILs; PD-1/PD-L1 and TILs; and prognostic studies of TILs across various cancers. Keyword and reference analyses further indicate that "adoptive cell therapy," "the prognostic value of TILs," and "immune checkpoint inhibitors and TILs" are central themes in current and future research. Combination therapies; tumor neoantigens; gene editing; dominant population selection of TILs therapy; TILs in Tumor microenvironment; emerging predictive biomarkers; TILs in predicting the efficacy of neoadjuvant chemotherapy and immunotherapy; the relationship between TILs and PD-L1; TIL-based patient stratification; tertiary lymphoid structures; and TIL evaluation through digital pathology and artificial intelligence are identified as key areas of interest. This analysis highlights the increasing academic focus on tumor-infiltrating lymphocyte research and identifies key recent themes in the field such as prognostic value of TILs, personalized treatments, and combination therapies.